2008
DOI: 10.1016/j.jacc.2008.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Risks of Restenosis and Stent Thrombosis in Bare-Metal Versus Drug-Eluting Stents

Abstract: A small absolute increase in DES thrombosis compared with BMS after 1 year (>0.14%/year) would result in BMS being the preferred strategy for the overall PCI population. Larger clinical trials with longer follow-up are needed to estimate the risk of late stent thrombosis with greater certainty for existing and new DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 43 publications
1
42
2
2
Order By: Relevance
“…Garg and colleagues reported a small increase in DES thrombosis compared with BMS after one year (>0.14%/year). 8 This rate is, however, considerably lower than that reported by Daemen and Wenaweser and colleagues, who found that LST occurs in both DES at a steady rate of 0.5 % per year during follow-up up to four years, but in this report BMS were not included. 9,10 Their overall results suggest that LST was slightly, but significantly more frequent with PES than with SES (cumulative incidence at four years of 3.6 vs. 2.7% respectively, p=0.02), but this was mainly due to a Late stent thrombosis, endothelialisation and drug-eluting stents different outcome during the first year (2.0 vs. 1.3% respectively).…”
contrasting
confidence: 59%
“…Garg and colleagues reported a small increase in DES thrombosis compared with BMS after one year (>0.14%/year). 8 This rate is, however, considerably lower than that reported by Daemen and Wenaweser and colleagues, who found that LST occurs in both DES at a steady rate of 0.5 % per year during follow-up up to four years, but in this report BMS were not included. 9,10 Their overall results suggest that LST was slightly, but significantly more frequent with PES than with SES (cumulative incidence at four years of 3.6 vs. 2.7% respectively, p=0.02), but this was mainly due to a Late stent thrombosis, endothelialisation and drug-eluting stents different outcome during the first year (2.0 vs. 1.3% respectively).…”
contrasting
confidence: 59%
“…23 Because there are no published data on the utility decrement associated with LAA occlusion, we assumed this to be the same as that associated with a percutaneous coronary revascularization procedure. 38 Additional utility decrements were applied if a procedure-related complication (eg, stroke) occurred.…”
Section: Quality-of-life Estimatesmentioning
confidence: 99%
“…This is in agreement with a study showing that patients who benefit most from DES in terms of net clinical outcome are those at higher risk of restenosis, including patients with diabetes. 22 Of note, DM patients with bifurcation lesions had worse long-term outcomes than patients without, regardless of stent type, consistently with other PCI settings. 23,24 In fact, DM is characterized by a variety of mechanisms responsible for accelerated atherosclerosis affecting the entire coronary circulation, 25,26 and DES does not address nontarget lesions related to disease progression and plaque rupture.…”
Section: Capodanno Et Al Bifurcations In Patients With Diabetes Mellitusmentioning
confidence: 66%